Analisis Aspek Usability pada Website PDAM XYZ Kota XYZ dengan Metode WEBUSE - Fahri, Muhammad; Ratmananda, Diasta; Zulfikar, M. Rizki; Putri, Risky Setiani; Natasia, Sri R. (Teknik Informatika Universitas Pamulang, 2021)
Website usability is very important because it can determine and know the quality related to how easily the user can use and learn and learn and whether the website runs in sync according to function and does not cause errors at the time of use. Each website has a different level of usability, the increased level of usability means that the website is easier to understand users (users can easily find what users are looking for quickly and not experience problems). This research aims to find out if the website has met the needs of users and know the difficulties experienced by users. This case study researchers chose the PDAM XYZ website of XYZ city. With the implementation of usability, it is expected that PDAM XYZ will know what is needed by users to access the PDAM XYZ website. Research on the website PDAM XYZ XYZ city is using the web usability evaluation tool (WEBUSE), WEBUSE method is a convenience evaluation method in the form of a web-based ease of use evaluation questionnaire to assess the usefulness of the website being evaluated. Researchers conducted an analysis by taking a sample of 20 users of PDAM XYZ Kota XYZ website. Based on the research that has been done obtained good and excellent results on the four variables, obtained the highest variable is the variable Content, Organization and Readability with a score of 0.89, and the lowest variable is Performance & Effectiveness which gets a score of 0.68.